The psychometric properties of the WISC-IV verbal comprehension and working memory indices among visually impaired students in Sudan - Alhaj Salih, Mohamed Abdalazeem; Khalil, Abeer Abdelrahman; Bakhiet, Salaheldin Farah Attallah (Frontiers in Psychology, 2025)
BackgroundIntelligence testing in Sudan began in 1946, with efforts to adapt and validate international assessments starting in 1964. However, no intelligence test had been specifically tailored for students with visual impairments.AimsThis study aimed to fill this gap by adapting the Verbal Comprehension and Working Memory indices of the WISC-IV for use with visually impaired children and assessing their reliability and validity.MethodsThe study involved 166 visually impaired students (57.83% male, 42.17% female), aged 6–16 years, drawn from schools in Khartoum.ResultsThe adapted indices demonstrated strong reliability and validity, supporting their suitability for use with Sudanese students who have visual impairments.ConclusionThe findings support the use of the adapted Verbal Comprehension and Working Memory indices to assess verbal intelligence in visually impaired students in Sudan for both diagnostic and evaluative purposes.